Answer:
B
Step-by-step explanation:
Given that ;
f(x)= x³
f(x)-4 = x³- 4
See attached graph using the graph tool
Answer:
4x - 3y = 2
Step-by-step explanation:
First, let's review what "standard form" signifies: Ax + By = C.
Starting with y = 4/3 * x - 2/3, multiply all three terms by 3 to eliminate the fractions:
3y = 4x - 2
Next, subtract 3y from both sides:
0 = 4x - 3y - 2.
It would be nice (tho' not essential) to have the coefficient of x positive. That is why I've left 4x on the right side and subtracted 3y from both sides.
finally, add 2 to both sides, obtaining 4x - 3y = 2. This is the equation in standard form.
Answer:
121
Step-by-step explanation:
it is what it is